Screening Indicators for an Improved Faculty Accomplishment (Recoletos Multidisciplinary Research Journal, 2016)
This study determined the indicators for an improved faculty accomplishment based on selected profile (age, the number of years of teaching, performance rating, and salary), Common Criteria for Evaluation or CCE (educational qualification, professional achievements, and academic experience) and Qualitative Contribution Evaluation (QCE) ratings. One hundred percent (160) of faculty with ratings in the NBC- 461 6th cycle comprised the respondent which was evidently adequate as sample based on Kaiser?Meyer?Olkin (KMO) results. The Bartlett?s test of sphericity indicates that variables are well-defined for Principal Component Analysis (PCA). The pre-defined indicators were categorized as indexes labeled as Input-Process-Output-Outcome. Results show that change in the Outcome of HE varies depending on the variables involved in the analysis. Considering full data, data with QCE and data of senior faculty, Inputs, Processes, and Outputs significantly contribute towards an improved (Outcome) faculty accomplishment (FA). The analysis on junior faculty (JF), showed that only Inputs and Outputs were significantly affecting change on Outcome of HE. Moreover, the most significantly affecting indicators towards faculty accomplishments are performance rating, age, and number of years of teaching. Then educational qualification followed, next are professional achievement and academic experience, and lastly the QCE.
Keywords: faculty accomplishment; screened indicators; improved accomplishment; pca on achievement; ipoo on faculty accomplishment